Digital Consumer Engagement: National Cultural Differences and Cultural Tightness. Issue 4 (December 2021) - Mattison Thompson, Frauke; Brouthers, Keith D.
The digital ecosystem makes entry into foreign markets easier and provides new ways for consumers to engage with marketing materials (through content clicking, sharing, and electronic word-of-mouth [eWOM] behavior). While evidence has emerged that between-country cultural differences may impact digital consumer engagement (particularly eWOM), far less is known about its impact on online advertising clicking and sharing engagement or how within-country cultural variation (tightness/looseness) moderates this activity. The authors develop and test the notion that between- and within-country cultural differences lead to variations in digital consumer engagement, especially clicking and sharing behavior. Using industry data provided by a programmatic advertising firm, the authors find support for the idea that between-country differences in national cultural values impact digital engagement and that within-country cultural variation moderates these relations. In this way, they provide new insights for researchers and managers about international marketing in the digital age.